Pengembangan E-Modul IPA Tema 6 Subtema 2 Materi Siklus Hidup Hewan Berbasis Problem Based Learning Berbantu Flipbook Maker di Kelas IV Sekolah Dasar - Friska, Sonia Yulia; Nurhalida, Nurhalida; Susilawati, Wiwik Okta (JEMS: Jurnal Edukasi Matematika dan Sains, 2022)
process of science e-module teaching materials and student responses to science e-module teaching materials. This study uses the ADDIE model. This trial was carried out on 24 students in Class IV Elementary School 01 Sitiung Dharmasraya. Data collection techniques were carried out with validation tests, educator response questionnaire tests and student response questionnaire tests. The results of the researchers obtained that the science e-module was obtained with the evaluation criteria for the validation of language, media and material with the results (86.30%) categorized as very valid. The practical aspect of the questionnaire responses of educators and students with a percentage (83, 22 % ) is categorized as very practical. Then it was concluded that the e-module Science theme 6 sub-theme 2 was problem-based learning animal life cycle material with the help of a flipbook maker in the fourth grade of elementary school. Attractive and feasible to use and able to improve the learning abilities of students.